INTERNATIONAL POLITICAL ECONOMY OF NIGERIAN AMALGAMATION SINCE 1914 - Mohammed, Usman (European Scientific Journal, ESJ, 2013)
This work examines the politics surrounding the idea and process of amalgamating the areas later to be known as Nigeria. The central problematic of the work rests on the attempt to answer, how, the politics of the two Nigerias was a means to achieving political and economic ends by the amalgamators. Using both primary and secondary data predicated on the Realist Theory, the work has attempted to establish the historical relationship between the Great Britain i.e. the amalgamators and the United Nigeria, as the amalgamated. The paper argues that, since 1914 the interaction between the two entities is characterized by statism, self-help, and survival, with Nigeria been the junior partner at the receiving end and worse-off. The paper found that the triad conspiracy between the Nigerian traditional leaders, the former colonial rulers and the current military and political forces is still alive and kicking at the detriment of the citizenry. Finally, the work recommend that Nigeria should be rational in formulating and executing both its domestic and foreign policies so as to forestall the chances of losing the next century as it did the last one.